Smart car parking system model for urban areas - Rahman Atiqur (Computer Science and Information Technologies, 2021)
This article is on the smart car parking system. In which we going to utilize the ultrasonic sensor to distinguish the vehicle and it will assist the proprietor with finding an advantageous parking spot. Parking spots are significant in city urban areas. In view of the expansion in a huge number of vehicles, the requirement for parking spots is a need, and henceforth an earnest needs to build up a system that can deal with these parking spots. To determine these necessities we build up a system to show the empty path in the parking spots. This includes a system that incorporates an ultrasonic sensor, raspberry pi 4, wifi-module, and a led show outside the vehicle parking entryway. Parking spots are observed by the staff of the concerned power. The paper incorporates the subtleties of parts that are utilized and about the working of this system. The paper likewise shows that our system's looking through an ideal opportunity to locate a free spot is more productive than some other existing system.